Symposium on Public Policy Issues in Finance - LELAND, HAYNE E.; FELDSTEIN, MARTIN; GLAUBER, ROBERT R.; MULLINS, DAVID W.; WALLMAN, STEVEN M. H. (Journal of Finance, 1997)
ABSTRACT The thesis of this symposium, organized by James Bicksler, was that while finance theory will surely inform practitioners, it seems appropriate to pay some attention to the opposite flow: practitioners can inform theory. Contributors include a distinguished group of practitioners with extensive backgrounds in economics, and economists with extensive public policy experience: Martin Feldstein, Robert Glauber, David Mullins, and Steven Wallman. Their topics range from privatizing social security, to managing market crashes, to the regulatory agency cost problem, to regulatory constraints in a technologically advanced world.